Restructuring State-Owned Enterprises (SOEs) as a Strategy to Face Demonopolization Policies - Samawati Saleh, Putu (Media Hukum, 2019)
The demonopolization policy on State-Owned Enterprises (SOEs) makes SOEs as an independent corporations by prioritizing profit motives while running a business for public benefits. The opportunity for private companies to become competitors of SOEs that have been running a monopoly business is one of the challenges for SOEs to compete. Restructuring of SOEs is a strategy to survive in business. The fundamental goal to achieve is that SOEs can become the main business entity that plays a role in national development by combining corporate/business principles and public services, but it still rests on the concept of democratic economy as a characteristic of Indonesian. The main problem to improve the role of SOEs in being able to be independent and competitive would be presented through normative juridical (doctrinal) research by using secondary data as the main data. The findings in the normative-prescriptive analysis would then be interacted using qualitative descriptive analysis methods through inductive conclusions. The results is finding an external and internal improvement strategy for the company by strengthening the concept of restructuring as an effort to enhance the role SOEs to be independent, competitive, and contributive to the sovereign, fair, and prosperous national economy.